Interface Magnetism in La0.7Ca0.3MnO3/PrBa2Cu3O7 Epitaxial Heterostructures. Issue 19 (24th July 2018) - Cuellar, Fabian A.; Hernandez‐Martin, David; Tornos, Javier; Gallego, Fernando; Orfila, Gloria; Rivera‐Calzada, Alberto; Sefrioui, Zouhair; Leon, Carlos; Santamaria, Jacobo
Abstract : All oxide magnetic tunnel junctions based on epitaxial La0.7 Ca0.3 MnO3 (LCMO)(8 nm)/PrBa2 Cu3 O7 (PBCO) (3–8 nm)/LCMO(25–50 nm) heterostructures grown on (100) SrTiO3 are examined. Manganite electrodes show large (bulk‐like) magnetic moments and exhibit different magnetic anisotropies with different easy axes directions. A form of low dimensional magnetism is induced at the interfaces by the superexchange interaction across the reconstructed bonds. It acts as an exchange spring, driving ferromagnetic coupling between the electrodes. Resistance versus magnetic field loops demonstrate that the interfacial coupling strength depends on electric field through its effect on electronic reconstruction and orbital hierarchy at the interface. The electrically controlled magnetic coupling between the magnetic moments of the electrodes signals a new path toward low dissipation spintronics. Abstract : The emergent electronic states at the interface between correlated oxides are a source of exciting novel device concepts. The induced magnetism resulting from orbital reconstruction at the barrier/electrode interfaces of a magnetic tunnel junction triggers a novel form of ferromagnetic coupling between magnetic electrodes has been showed. This coupling is electrically controlled and enables electric field switching of the magnetization, drawing a new strategy toward low dissipation spintronics.